Analisis Nilai Karakter Disiplin Siswa Kelas V SDN Purwoyoso 01 Kota Semarang - Triginawati, Nurul Hidayah; Shabhira, Helmita Hana; Kavina, Hufadz Nadiyya; Noor Azizah, Wafiyatul ‘Ahdi; Kiptiyah, Siti Maryatul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The instillation of character education in schools is carried out through the Pancasila Education learning process which aims to develop character values, one of which is the value of discipline. The objectives of this research are (1) Knowing the value of student discipline activities in the classroom, 2) Factors that influence student discipline, 3) Challenges in building student discipline character in the classroom, 4) Strategies for developing student discipline character. The results of this research show that (1) The value of disciplinary activities is assessed from attendance recaps, praying before studying, being orderly when lessons start, collecting assignments on time, not making noise, and carrying out pickets according to schedule. (2) Factors that influence student discipline are the influence of peers who are less supportive. (3) The challenge in building students' disciplined character is that the level of student discipline certainly differs from one student to another. (4) The strategy used to develop disciplined character is by instilling positive habits, character development through extra-curricular activities, and through the implementation of portfolio assignments. This research uses descriptive qualitative methods.